(untitled) (SCIÉNDO INGENIUM, 2022)
The research aimed to: Determine the in vitro antibacterial effect of the hydroalcoholic extract of Solanum melongena L (Eggplant) in 3 concentrations, on strains of Streptococcus mutans ATCC 25175, Material and Methods: The susceptibility test, using the disk procedure with Mueller Hinston culture medium, in three concentrations of 25%, 50%, 75% of hydroalcoholic extract of Solanum melongena L and 0.12% chlorhexidine as positive controls. It was prepared and incubated at 37°C in microanaerobiosis. The reading took place after 24 and 48 hours, in each of the concentrations the inhibition halo was calculated with a millimeter ruler. Results: Taking into account the Duraffourd scale, the reading was achieved and the strain of streptococcus mutans ATCC 25175 was observed, showing a limit sensitivity to the concentration of 75% of the hydroalcoholic extract of Solanum melongena L as well as 0.12 chlorhexidine. %. Conclusion: The hydroalcoholic extract of Solanum melongena L presented antibacterial effect "in vitro" on strains of streptococcus mutans ATCC 25175.